Differences of Power and Torsion Output in One Cylinder Motorcycle - Muharam Yuli Prasojo (HM Publisher, 2021)
The purpose of this literature review is to describe the differences of power, torsion, and fuel consumption output of an one cylinder motorcycle which given ignition system variances between CDI standart, CDI racing, standart spark plug, and iridium spark plug used three kinds of gasoline premium, pertamax, and pertamax plus. minimum fuel consumption can be obtained by reduce the ignition system which followed by appropriate octane gasoline usage in this case reduce the ignition system into CDI racing kurva 2 and standart spark plug using pertamax gasoline.